Participatory eco-development in question: - Lucie Dejouhanet (Revue de Géographie Alpine)
While Indian forest policies have evolved from a directive paradigm to a participative one, protected areas are still managed by legislative acts, which advocate a clear separation between human activities and areas to be protected. Eco-development financed by the World Bank was planned as a tool for developing alternative activities to resource exploitation and for involving local populations in environment protection through participation. Started in 2001 in the Wildlife Sanctuary of Parambikulam in Kerala, its results few years after are rather inconclusive. While a report in 2003 was accusing the social disintegration of concerned people, I am more stressing on the inappropriateness of EDC to villages’ context. The essentialist cliché attached to adivasi people is an a-historical viewpoint, which does not allow thinking local development today. Eco-development, for reaching its goals, has to permit a real negotiation between protected area actors and to propose realistic compromises between restraining activities and allowing population survival.